2016
DOI: 10.1108/intr-05-2014-0136
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intrinsic and extrinsic motivations on mobile coupon sharing in social network sites

Abstract: Purpose – The purpose of this paper is to investigate the influence of two intrinsic (i.e. sense of self-worth and socializing) and two extrinsic motivations (i.e. economic reward and reciprocity) on mobile coupon (m-coupon) sharing by users in social network sites (SNSs). Moreover, this study examines how coupon proneness moderates the relationship between motivations and m-coupon sharing in SNSs. Design/methodology/approach – A researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 63 publications
0
62
1
4
Order By: Relevance
“…Some have hailed the use of different social media platforms as the next source of competitive advantage (Ahi et al, 2017;Alarcon et al, 2015;Christodoulides et al, 2015;Jun and Park, 2017;Tang et. al., 2016;Siamagka et al, 2015;Neeley and Leonardi, 2018;Wang, Tian, and Li, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some have hailed the use of different social media platforms as the next source of competitive advantage (Ahi et al, 2017;Alarcon et al, 2015;Christodoulides et al, 2015;Jun and Park, 2017;Tang et. al., 2016;Siamagka et al, 2015;Neeley and Leonardi, 2018;Wang, Tian, and Li, 2019).…”
mentioning
confidence: 99%
“…Moreover, organizations are increasing their presence on many social media platforms (Ahi et al, 2017;Michaelidou et al, 2011;Tang et al, 2016;He et al, 2019). As a result, many scholars have been motivated to study the use of social media to communicate with customers, widen their experience (Wilson et al, 2011;Nisar, Prabhakar, and Strakova, 2019), and employ social media strategy to reach consumers (Kietzmann et al, 2011;Duff & Segijn, 2019).…”
mentioning
confidence: 99%
“…The values of composite reliabilities and Cronbach's α are higher than the threshold of 0.70 [69, 70]. The values of AVE are all higher than 0.50 [71, 72]. …”
Section: Resultsmentioning
confidence: 99%
“…Further, these two main antecedents are also linked. Behavioral studies demonstrated a positive relationship between the utilitarian value (or extrinsic motivation) and hedonic value (or intrinsic motivation) associated with the use of a technology (Chang, Liu, & Chen, 2014;Davis et al, 1992;Deci & Ryan, 1985;van der Heijden et al, 2005;Tang, Zhao, & Liu, 2016). Venkatesh and collaborators made a step further and suggested that there is, in fact, a positive influence of intrinsic motivation over perceived usefulness associated with a technology use (Venkatesh, 1999;Venkatesh et al, 2002) because intrinsic motivation increases enjoyment regarding the fulfillment of a task resulting in a higher quality and productivity in a broader sense.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%